Postoperative throat discomfort and associated factors among surgical patients at Ethiopian Teaching Hospitals: cross-sectional study - Hunduma Jisha; Zenebe Bekele (Ain Shams Journal of Anesthesiology, 2023)
Abstract Background Throat pain and airway discomfort are the most commonly upsetting conditions for patients’ wellbeing after surgery. However, little is known about the problem and associated factors, especially in developing countries like Ethiopia. Therefore, this work determined the magnitude, severity, and associated factors of throat discomfort within 24 h after elective surgery. Results The majority (63.2%, or 211) of the participants were female, with a mean age of 35.7 ± 9.7 years. The overall postoperative throat discomfort was observed in 122 (36.5%) patients, and it was severe in 20.5% of them. However, the severity level declined over time to 21.9% (21/96), 15.3% (18/118), and 5.6% (5/89), respectively, on the 1st, 6th, and 24th hours, as indicated by participants. Utilization of a larger ETT (AOR = 6.26, CI 2.13–18.43, P = 0.001), surgery lasting two or more hours (AOR = 11.20, CI 3.53–35.50, P = 0.000), awake extubation (AOR = 0.16, CI 0.05–0.43 P = 0.000), frequent episodes of hypotension (AOR = 12.85, CI 4.56–36.18, P = 0.000), and a less experienced anesthetist (AOR = 18.10, CI 6.51–50.31, P = 0.000) were significantly associated with throat discomfort. Conclusions Post-extubation throat discomfort complaints are high (36.5%). Due attention has to be given to minimize or prevent perioperative frequent episodes of hypotension, higher ETT size utilization, blood loss, and the duration of surgery as much as possible. Postoperative throat discomfort should not be ignored. And we recommend that patient reassurance and orientation with analgesia has to be considered during the postoperative period.